Cholesterol localization around the metabotropic glutamate receptor 2 - Kurth, Markus; Lolicato, Fabio; Sandoval-Perez, Angelica; Amaya-Espinosa, Helman; Teslenko, Alexandra; Sinning, Irmgard; Beck, Rainer; Brügger, Britta; Aponte-Santamaria, Camilo (The journal of physical chemistry. B, Biophysics, biomaterials, liquids, and soft matter, 2020)
The metabotropic glutamate receptor (mGluR) 2 plays a key role in the central nervous system. mGluR2 has been shown to be regulated by its surrounding lipid environment, especially by cholesterol, by an unknown mechanism. Here, using a combination of biochemical approaches, photo-cross-linking experiments, and molecular dynamics simulations we show the interaction of cholesterol with at least two, but potentially five more, preferential sites on the mGluR2 transmembrane domain. Our simulations demonstrate that surface matching, rather than electrostatic interactions with specific amino acids, is the main factor defining cholesterol localization. Moreover, the cholesterol localization observed here is similar to the sterol-binding pattern previously described in silico for other members of the mGluR family. Biochemical assays suggest little influence of cholesterol on trafficking or dimerization of mGluR2. Nevertheless, simulations revealed a significant reduction of residue-residue contacts together with an alteration in the internal mechanical stress at the cytoplasmic side of the helical bundle when cholesterol was present in the membrane. These alterations may be related to destabilization of the basal state of mGluR2. Due to the high sequence conservation of the transmembrane domains of mGluRs, the molecular interaction of cholesterol and mGluR2 described here is also likely to be relevant for other members of the mGLuR family.
Gesehen am 25.11.2020